The role of small molecules in cell and gene therapy. Issue 3 (24th December 2020) - Brayshaw, Lewis L.; Martinez-Fleites, Carlos; Athanasopoulos, Takis; Southgate, Thomas; Jespers, Laurent; Herring, Christopher
Abstract : Current and future uses of small molecules to improve the safety, efficacy and manufacturing of cell and gene therapies. Abstract : Cell and gene therapies have achieved impressive results in the treatment of rare genetic diseases using gene corrected stem cells and haematological cancers using chimeric antigen receptor T cells. However, these two fields face significant challenges such as demonstrating long-term efficacy and safety, and achieving cost-effective, scalable manufacturing processes. The use of small molecules is a key approach to overcome these barriers and can benefit cell and gene therapies at multiple stages of their lifecycle. For example, small molecules can be used to optimise viral vector production during manufacturing or used in the clinic to enhance the resistance of T cell therapies to the immunosuppressive tumour microenvironment. Here, we review current uses of small molecules in cell and gene therapy and highlight opportunities for medicinal chemists to further consolidate the success of cell and gene therapies.